FACTORS INFLUENCING THE PHARMACEUTICALLY IMPORTANT CHARACTERISTICS OF LOBELIA INFLATA L. - Máthé, A.; Szöke, E.; Kursinszki, L.; Hájos, M. T. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Lobelia inflata L. (Lobeliaceae) contains pharmacologically important secondary metabolites, which consist of more than 20 piperidine alkaloids. Lobeline with its stimulatory effect on the respiratory centre is used in anti-smoking preparations. The pharmaceutical importance could be improved by the polyacetylenes (lobetyol, lobetyolin, lobetyolinin). The main goal of the experiments: to introduce the species into field production in Hungary and to identify the factors influencing its pharmaceutically important characteristics. Plantlets were propagated and raised both in vitro and in vivo. After acclimatization in a glass-house they were transplanted to irrigated open field conditions at 4 Hungarian locations. In vitro organized cultures produced intensive growth and considerable secondary metabolites. In contrast to lobetyolin (polyacetylene), the alkaloid (lobeline) content decreased in the open field. The effect of nutrient supply was also considered. Phytochemical analyses revealed differences in the total alkaloid content, both in view of the geographic region of cultures and the propagation technology. The highest alkaloid and polyacetylene contents were detected in the population grown at Mosonmagyaróvár. Lobetyolin content exceeded in all samples the content of lobetyolinin. No similar differences were observed with lobeline. Field grown plants contained sufficient amounts of active principles. The nearly 1 t/ha biomass yield and active substance production could be increased by higher plant density and fertilization. N-fertilization increased the above ground phytomass, due to the increased number of side-branches. Dry mass was highest under the influence of MgSO4 (2%) foliar spraying. A similarly positive influence was detected both in the total alkaloid production and the lobeline content. As a contrast, a decrease in the total alkaloid content was observed with the doubling of both polyacetylenes. Acknowledgements: GVOP 3.1.1.-0309/3